Small Area Estimation Untuk Mengestimasi Persentase Kebutuhan Rumah Sederhana di Kabupaten Buleleng - Luh Devi Maharani Mecker; I Komang Gde Sukarsa; I Wayan Sumarjaya (Jurnal Matematika, 2025)
Data is a source of information to support the decision-making process of the object under study so that the availability of data is important to fulfill. Survey as one of the techniques used to provide data has weaknesses such as area parameters outside the design cannot be explained by the statistics generated. Small area estimation (SAE) is an indirect estimator method that can overcome the problems of survey data. SAE is used to estimate population or subpopulation parameters with limited sample size to produce statistics that are as precise as direct estimators. The general approach used in SAE is EBLUP. The topic in this research is the need for simple houses in Buleleng Regency. By estimating the percentage of simple housing needs for each sub-district in Buleleng through direct estimation and EBLUP, the results show that the estimation value of the direct estimator is not more precise than EBLUP indicated by the MSE output of the direct estimator which is greater than EBLUP. Based on the output of the estimation results with the EBLUP method, the results show that the highest and lowest percentage of housing needs are in Sukasada Sub-district at 67.05% and Banjar Sub-district at 37.19%, respectively.